2012
DOI: 10.1152/ajpregu.00301.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects and possible mechanisms of acupuncture at ST36 on upper and lower abdominal symptoms induced by rectal distension in healthy volunteers

Abstract: Background acupuncture (AP) has been shown to have a therapeutic potential for gastrointestinal motility disorders. The aims of this study were to investigate the effects and possible mechanisms of acupuncture on postprandial upper and lower abdominal symptoms induced by rectal distension (RD). Twenty healthy volunteers were involved in a two-session study (AP and sham-AP, AP and no-AP, or sham-AP and no-AP). In 12 of the volunteers, RD was performed for 60 min in the postprandial state, and AP at ST36 or sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…There have been a few studies exploring the correlation between the changes of gastric motility and automatic activity in response to acupuncture/EA at ST36. The vagal mechanism was reported in the effects of acupuncture/EA at ST‐36 on gastric motility and upper abdominal symptoms . In the present study, a substantial increase in HF vagal activity and a decrease in LF sympathetic activity were noted with TEA at ST36, and these effects might have antagonized the effects of the cold stress on the autonomic functions, resulting in normalization of gastric slow waves under the stress.…”
Section: Discussionsupporting
confidence: 56%
“…There have been a few studies exploring the correlation between the changes of gastric motility and automatic activity in response to acupuncture/EA at ST36. The vagal mechanism was reported in the effects of acupuncture/EA at ST‐36 on gastric motility and upper abdominal symptoms . In the present study, a substantial increase in HF vagal activity and a decrease in LF sympathetic activity were noted with TEA at ST36, and these effects might have antagonized the effects of the cold stress on the autonomic functions, resulting in normalization of gastric slow waves under the stress.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have investigated ameliorating effects of acupuncture or EA on gastrointestinal motility and symptoms . Acupuncture or EA at ST36 has been reported to improve gastrointestinal symptoms such as nausea, vomiting, fullness, satiety and bloating, and to treat digestive diseases . Previous studies from our laboratory revealed EA at ST36 was also able to improve gastric dysrhythmias and antral hypomotility as well as delayed GE, abdominal symptoms induced by RD in dogs .…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies using the spectral analysis of HRV to explore the autonomic mechanisms of acupuncture/EA at ST36. Most previous studies reported that the effects of acupuncture/EA on gastric dysrhythmias were mediated via the vagal mechanism . In region‐specific effects of acupuncture, Takahashi and co‐workers demonstrated that EA at ST‐36 decreased the ratio of LF/HF in normal rats, suggesting excitatory gastric responses were mediated via the vagal pathway .…”
Section: Discussionmentioning
confidence: 99%
“…A lower vagal tone and higher sympathetic tone were reported in FD patients, compared with healthy persons [2123]. EA has been consistently shown to regulate autonomic function in clinical and animal studies [27, 40]. Previously AEA on the concha of the ear was shown to increase vagal activity in healthy men [41].…”
Section: Discussionmentioning
confidence: 99%